2011
DOI: 10.1152/ajprenal.00515.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin/receptor expression in urinary bladder of mice with overexpression of NGF in urothelium

Abstract: Urothelium-specific overexpression of nerve growth factor (NGF) in the urinary bladder of transgenic mice stimulates neuronal sprouting in the urinary bladder, produces increased voiding frequency, and results in increased referred somatic hypersensitivity. Additional NGF-mediated pleiotropic changes might contribute to the increased voiding frequency and pelvic hypersensitivity observed in these transgenic mice, such as modulation of other growth factor/receptor systems. Chronic overexpression of NGF in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 62 publications
7
53
0
3
Order By: Relevance
“…Thus various stimuli can lead to secretion of chemical substances capable of modulating the activity of underlying smooth muscle (141,271), as well as nearby sensory neurons. For example, urothelial-specific overexpression of nerve growth factor (NGF) results in increased bladder nerve "sprouting" and increased voiding frequency (119,251). It has been shown that urothelial-derived NO can be released in response to mechanical as well as chemical stimulation and may either facilitate or inhibit the activity of bladder afferent nerves conveying bladder sensation (18,42).…”
Section: Urothelium-lamina Propria Interactionsmentioning
confidence: 99%
“…Thus various stimuli can lead to secretion of chemical substances capable of modulating the activity of underlying smooth muscle (141,271), as well as nearby sensory neurons. For example, urothelial-specific overexpression of nerve growth factor (NGF) results in increased bladder nerve "sprouting" and increased voiding frequency (119,251). It has been shown that urothelial-derived NO can be released in response to mechanical as well as chemical stimulation and may either facilitate or inhibit the activity of bladder afferent nerves conveying bladder sensation (18,42).…”
Section: Urothelium-lamina Propria Interactionsmentioning
confidence: 99%
“…Thus dissected, the urothelium also includes suburothelial structures; the term "urothelium" in this article refers to both urothelial and suburothelial structures. Total RNA was extracted using the STAT-60 total RNA/mRNA isolation reagent (Tel-Test "B"; Friendswood, TX), as previously described (5,26). One to 2 g of RNA per sample were used to synthesize cDNA using SuperScript II reverse transcriptase and random hexamer primers with the SuperScript II Preamplification System (Invitrogen, Carlsbad, CA) in a 20-l final reaction volume.…”
Section: Ccl2 and Ccr2 Transcript Expression In Urinary Bladder: Qrt-pcrmentioning
confidence: 99%
“…Real-time qRT-PCR was performed using SYBR Green I detection (5,26). cDNA templates, diluted 10-fold to minimize the inhibitory effects of the reverse transcription reaction components, were assayed using HotStart-IT SYBR Green qPCR Master Mix (USB, Cleveland, OH) containing 5 mM MgCl 2, 0.4 mM dATP, dGTP, dCTP, and dTTP, HotStart-IT Taq DNA polymerase, and 300 nM of each primer in a final 25-l reaction volume.…”
Section: Ccl2 and Ccr2 Transcript Expression In Urinary Bladder: Qrt-pcrmentioning
confidence: 99%
“…The expression of TrkB is also abundant in sensory neurons innervating the bladder wall Murray et al, 2004). Like in somatic tissue Thompson et al, 1999), BDNF expression in the bladder seems to be under the control of NGF (Schnegelsberg et al, 2010;Girard et al, 2011). BDNF appears to be a key participant in bladder dysfunction in an animal model of cystitis as its sequestration improved both bladder reflex activity and peripheral hypersensitivity (Frias et al, 2009;Pinto et al, 2010a).…”
Section: Brain Derived Neurotrophic Factor (Bdnf)mentioning
confidence: 99%